Mind the Gap: The Implications of Not Acting in Line With Your Planned Actions After Installing Solar Photovoltaics - Peters, Annemijn Maron; van der Werff, Ellen; Steg, Linda (Frontiers in Psychology, 2019)
To realize the full potential of solar photovoltaics (PV), PV adopters need to adapt their energy demand to the production of self-generated solar energy as much as possible (i.e., use their PV sustainably). In a longitudinal questionnaire study (N = 74) in the Netherlands, we compared the intention to use PV in a sustainable way before the installation of PV with actual PV use. Wave 1 took place before respondents adopted PV, while Wave 2 took place after they installed PV. We examined whether potential differences between actual sustainable PV use and initial intentions may have implications for how people see themselves and for the motivation they ascribe to their decision to adopt PV. Our results show that the vast majority of people use their PV in a less sustainable way than they anticipated. Furthermore, after the installation of PV, respondents are less likely to see themselves as a sustainable PV user and less likely to believe that PV have positive environmental consequences than before the installation, while environmental self-identity did not differ pre and post-installation of PV. Moreover, the stronger the discrepancy between intended and actual sustainable use of the PV, the less likely people were to see themselves as a sustainable PV user and as a person who acts pro-environmentally in general. These findings suggest that it is important to support people to use their PV in a sustainable way to facilitate them to act upon their intentions.